Effect of SiO2 interlayer on the properties of Al2O3 thin films grown by plasma enhanced atomic layer deposition on 4H‐SiC substrates. Issue 4 (28th October 2016) - Schilirò, E.; Fiorenza, P.; Di Franco, S.; Bongiorno, C.; Saggio, M.; Roccaforte, F.; Lo Nigro, R.
Abstract : Al2 O3 films were grown by plasma enhanced‐atomic layer deposition (PE‐ALD) on 4H‐SiC substrates, with and without the presence of a thin SiO2 layer. The collected data indicated the formation of amorphous, adherent, and uniform Al2 O3 thin films with a thickness of about 30 nm. The electrical characterization has been performed on metal–oxide–semiconductor (MOS) structures by both capacitance–voltage ( C – V ) and current–voltage ( I – V ) measurements. All these analyses demonstrated a better dielectric behavior of the Al2 O3 film deposited on the SiO2 /SiC stack, with respect to that deposited directly on the SiC substrate. In particular, higher dielectric constant value, lower leakage current density, and higher breakdown field have been found in the Al2 O3 /SiO2 /SiC stack. Hence, it has been argued that the presence of the interfacial SiO2 provides a better condition for the growth of high quality Al2 O3 films. In this context, the film density has been evaluated, and strong difference has been found in the density values, The correlation between the better electrical properties of the Al2 O3 films on SiO2 and their higher density has been demonstrated. These results provide useful insights on the possible application of these Al2 O3 films as gate insulator in 4H‐SiC metal‐oxide‐semiconductor field effect transistors.